2017
DOI: 10.1016/j.aninu.2016.11.003
|View full text |Cite
|
Sign up to set email alerts
|

Fermented soybean meal improves the growth performance, nutrient digestibility, and microbial flora in piglets

Abstract: In order to increase nutritive values of soybean meal (SBM), 3 species of microbes were used to ferment SBM. Through a 3 × 3 orthogonal design and parameter measurements of soybean peptide and anti-nutritional factor contents in the fermented soybean meal (FSBM), it was estimated that the best microbial proportion of Bacillus subtilis, Hansenula anomala and Lactobacillus casei was 2:1:2 for SBM fermentation (P < 0.05). The further piglet feeding experiment showed that 10% FSBM substitute for SBM had no signifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
62
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 87 publications
(72 citation statements)
references
References 20 publications
8
62
1
1
Order By: Relevance
“…In the current study, FRM demonstrated the same desirable effects on ADG, and intestinal development and barrier function as we have previously observed and optimum effects were observed when 8% or 10% FRM was included in the weaner diets [14]. Similar improvements in ADG upon dietary addition of FRM in broiler chicken [27] and fermented soybean meal in piglets [28,29] were reported in other studies. This beneficial effect could most likely be explained by the fact that supplementation of fermented feed may provide beneficial probiotic bacteria, such as lactic acid bacteria, and also prebiotic products produced during the pre-fermentation process [30,31].…”
Section: Discussionsupporting
confidence: 88%
“…In the current study, FRM demonstrated the same desirable effects on ADG, and intestinal development and barrier function as we have previously observed and optimum effects were observed when 8% or 10% FRM was included in the weaner diets [14]. Similar improvements in ADG upon dietary addition of FRM in broiler chicken [27] and fermented soybean meal in piglets [28,29] were reported in other studies. This beneficial effect could most likely be explained by the fact that supplementation of fermented feed may provide beneficial probiotic bacteria, such as lactic acid bacteria, and also prebiotic products produced during the pre-fermentation process [30,31].…”
Section: Discussionsupporting
confidence: 88%
“…However, such monosaccharide mixtures cannot be considered as a prebiotic because of the wellaccepted definition of prebiotic as a Bhost non-digestible food ingredient.^Obviously, hydrothermal pretreatment supernatant may include biomass-derived compounds that could affect bacteria (e.g., cause the slight inhibition of Enterobacteriaceae). However, the effects of this supernatant also resonate with the many recent studies (albeit still not fully supported by scientific investigations) showing observed improved robustness in gut health in pigs fed with fermented feed ingredients (e.g., fermented soya and rapeseed used as feed component [33][34][35]). Full elucidation of the active ingredients in the hydrothermal pretreatment supernatant is required to gain full insight into the mechanisms underlying the observed effects.…”
Section: Enzymatically Produced Xos and Axos From Ryegrassmentioning
confidence: 81%
“…Animal studies showed that digestibility of DM and CP was improved in fermented plant protein feed (Ni and Sun ; Yuan et al . ).…”
Section: Resultsmentioning
confidence: 97%